Nilai-Nilai Edukatif Peristiwa Tahkim Perang Shiffin (Kajian Ilmu Pendidikan Islam) - Sulaiman, Husnan; Pradana, Aji Mochammad (MASAGI : Jurnal Pendidikan Agama Islam, 2022)
Tahkim holds an important position in the history of Islamic politics. To date, the event of tahkim has often been presented from non-educational perspectives, such as politics, history, and culture. This research aims to offer a new approach by presenting the history of the tahkim event from the perspective of educational values. The objective of this study is to describe the educational values found in the tahkim event, which will then be presented within the framework of Islamic education studies. The method used is library research, followed by reading analysis using content analysis. In the data collection process, a descriptive-analytical approach was taken from various sources such as books, articles, and educational journals that are relevant to the content of this article. The research findings focus on four educational values in the tahkim event: religious values, Islamic brotherhood (ukhuwah Islamiyyah), tolerance, and morality. When linked to Islamic educational science, these educational values aim to raise human awareness, helping individuals grow and develop into religious, compassionate, tolerant, morally upright, and devoted worshippers of Allah SWT. Keywords: Educational Values, Tahkim, Battle of Siffin